The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1080/22221751.2022.2136537
|View full text |Cite
|
Sign up to set email alerts
|

Multiple genotypes of Crimean-Congo hemorrhagic fever virus detected in ticks during a one health survey in Agnam, Northeastern Senegal

Abstract: A Crimean-Congo Hemorrhagic Fever Virus (CCHFV) survey in Agnam (North Senegal) permits the detection of three isolates in ticks. These isolates belong genetically to multiple genotypes (I, II, III) and clustered with strains from Uganda, Sudan, Mauritania, and Senegal. The role of ticks in CCHF emergence and widespread is highlighted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 11 publications
1
5
0
Order By: Relevance
“…Previous studies on the CCHFV in Northern Senegal (Saint-Louis region) have repeatedly demonstrated its circulation among humans, ruminants, and ticks [ 25 ]. Human CCHF cases have been reported in areas in Northern Senegal, in Rosso in 2021, and in Podor in 2022 as well as in the northeast regions, including Bokidiawe in September 2019 [ 12 , 26 ] and Agnam Civol in 2021 [ 13 ]. Our study contributes new data on CCHF detection in Bokidiawe and marks its first detection in the Tambacounda region (Koumpentoum) in the southeast of the country.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous studies on the CCHFV in Northern Senegal (Saint-Louis region) have repeatedly demonstrated its circulation among humans, ruminants, and ticks [ 25 ]. Human CCHF cases have been reported in areas in Northern Senegal, in Rosso in 2021, and in Podor in 2022 as well as in the northeast regions, including Bokidiawe in September 2019 [ 12 , 26 ] and Agnam Civol in 2021 [ 13 ]. Our study contributes new data on CCHF detection in Bokidiawe and marks its first detection in the Tambacounda region (Koumpentoum) in the southeast of the country.…”
Section: Discussionmentioning
confidence: 99%
“…CCHFV strains were divided into several clades, which we labeled into genotypes based on the recent reclassification [10]. For both the L and S segments, our CCHF strains clustered with strains isolated in Mauritania in 1984 (ABB30015 and ABB30041), Spain in 2014 (ASV45882_SPN_2014 and ASV45880_SPN_2014), and Nigeria in 1996 and 1966 (AAY24690_NIG_1966 and ARB51456_NIG_1996_NIG) and other strains recently isolated in Matam, Senegal(Boki_CCHF_ 2019, ArD374334_SEN_2022, and ArD374517_SEN_2022) [12,13]. However, the genotypes of these two segments varied according to the genomic segments.…”
Section: Phylogenetic Analysesmentioning
confidence: 99%
See 2 more Smart Citations
“…Epidemiological and environmental data indicate that the northern regions of Senegal are at the highest risk of CCHF outbreaks [ 12 ]. This may be due to their ecological parameters and proximity to Mauritania where the CCHF epidemic is recurrent [ 13 , 14 ]. Indeed, the most recent strains/isolates were detected in Northern Senegal in the Matam region.…”
Section: Introductionmentioning
confidence: 99%